The effect of communication, teamwork, and work motivation on employee performance at PT X in Batam city - Talenta Br Sitepu; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2025)
This study investigates the influence of communication, teamwork, and work motivation on employee performance at PT X in Batam City. Using a quantitative research design, data were collected through structured questionnaires distributed to employees and analyzed using SPSS version 25. Statistical analyses, including t-tests and F-tests, revealed that communication, teamwork, and motivation each have a significant and positive effect on employee performance, both partially and simultaneously. The findings indicate that effective communication fosters clarity and cooperation, teamwork enhances collective productivity, and motivation drives employees to achieve organizational goals. These results are consistent with prior studies, confirming that organizational success strongly depends on the interplay between communication, teamwork, and motivation. The study concludes that strengthening these three factors can significantly improve employee performance and contribute to sustainable business growth at PT X.